2022
DOI: 10.3390/life12040546
|View full text |Cite
|
Sign up to set email alerts
|

Action Mechanisms of Small Extracellular Vesicles in Inflammaging

Abstract: The accumulation process of proinflammatory components in the body due to aging influences intercellular communication and is known as inflammaging. This biological mechanism relates the development of inflammation to the aging process. Recently, it has been reported that small extracellular vesicles (sEVs) are mediators in the transmission of paracrine senescence involved in inflammatory aging. For this reason, their components, as well as mechanisms of action of sEVs, are relevant to develop a new therapy ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…One such study found that LAPTM4B is upregulated in the lung tissues of patients with IPF, and that this upregulation is associated with increased oxidative stress and cellular injury (67), while another found that LAPTM4B is also upregulated in the lung tissues of patients with COPD and that this upregulation is associated with increased inflammation and oxidative stress (68). LAPTM4B has been shown to regulate the accumulation of oxidative stress and inflammation in vitro, as well as modulating the activity of enzymes involved in cellular senescence (69). However, more research is needed to fully understand the role of LAPTM4B in aging processes.…”
Section: Discussionmentioning
confidence: 99%
“…One such study found that LAPTM4B is upregulated in the lung tissues of patients with IPF, and that this upregulation is associated with increased oxidative stress and cellular injury (67), while another found that LAPTM4B is also upregulated in the lung tissues of patients with COPD and that this upregulation is associated with increased inflammation and oxidative stress (68). LAPTM4B has been shown to regulate the accumulation of oxidative stress and inflammation in vitro, as well as modulating the activity of enzymes involved in cellular senescence (69). However, more research is needed to fully understand the role of LAPTM4B in aging processes.…”
Section: Discussionmentioning
confidence: 99%